The Role of Social Security Program for Enhancing Seniors Longevity (Journal of Social Economics Research, 2020)
The United States’ social security system seeks to lower seniors’ probability of death. Given this strategic goal, the argument for the support of a government- managed social security program still shows greater promise than the program’s privatization. Americans seem to have greater wellness and longevity under the current government-run social security program. In fact, this program could explain the declining probability of death since the inception of the program. Conversely, many supporters of privatizing the social security system would highlight the huge opportunity costs for their contributions to the social security funds. Yet, many seniors may not withstand the possibility of sustaining financial losses in the volatile financial market. On the other hand, the proponents of the current government-run social security program may overlook potential interest and capital gains that could be realized if the contributions are invested in the private financial market. In a nutshell, social security is widely accepted as a part of the social safety net of the country aiming to improve senior citizens’ wellness and longevity. The social security, as a government-run institution may have come to stay.